Prestige and Dominance: How eWOM Differs Between Consumers High in Authentic and Hubristic Pride - Liu, Jiayao; Xiong, Qingyun; Zhong, Jianan (Frontiers in psychology, 2022)
Electronic word-of-mouth (eWOM) influences consumers' purchase decisions, but few studies have investigated the antecedents that lead consumers to create different types of eWOM. From the perspective of social interactions, this research explored how two subtypes of pride not only compel consumers to create eWOM but also differently impact four types of eWOM and their mechanisms. Study 1 manipulated the pride state and found that authentic pride promoted positive eWOM and constructive eWOM, while hubristic pride promoted negative eWOM and destructive eWOM. Study 2 examined the effect of pride on eWOM at the trait level and tested the mediating effect of their use of social status pursuit strategy. Overall, this study increases the understanding of different types of eWOM and broadens the literature of the effect of pride and social status pursuit strategy in the context of consumption.